2013
DOI: 10.1002/pssb.201349019
|View full text |Cite
|
Sign up to set email alerts
|

Flux-pinning properties of nanocrystalline HfO2 added YBa2 Cu3 O7−δ superconductor

Abstract: The effect of addition of different weight percentages of nanocrystalline HfO2, synthesized through a modified combustion method in bulk coarse‐grained orthorhombic YBa2Cu3O7−δ powder was studied. The structure and microstructure of the samples examined by X‐ray diffraction (XRD) and scanning electron microscopy (SEM) showed the formation of a secondary phase YBa2HfO5.5 in the superconductor without deteriorating the superconducting properties. The variation of sintering temperature, density, critical transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Due to the complexity of defects in polycrystalline superconductors several different pinning mechanisms may exist which are simultaneously active in polycrystalline high T c superconductors such as: dl pinning, due to the scatter of electron free path caused by the non-superconducting particles of the coherence length (n) embedded in the superconducting matrix and dj pinning, due to a spatial scatter of superconducting T c throughout the sample caused by other superconducting phases causing fluctuation in T c . However the optimum J c value observed for nano HfO 2 and BaHfO 3 added YBCO bulk in our earlier reports [27][28][29] was too low (in the ranges of 10 4 A/cm 2 ) compared to the present set of values (in the ranges of 10 6 A/cm 2 ).…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Due to the complexity of defects in polycrystalline superconductors several different pinning mechanisms may exist which are simultaneously active in polycrystalline high T c superconductors such as: dl pinning, due to the scatter of electron free path caused by the non-superconducting particles of the coherence length (n) embedded in the superconducting matrix and dj pinning, due to a spatial scatter of superconducting T c throughout the sample caused by other superconducting phases causing fluctuation in T c . However the optimum J c value observed for nano HfO 2 and BaHfO 3 added YBCO bulk in our earlier reports [27][28][29] was too low (in the ranges of 10 4 A/cm 2 ) compared to the present set of values (in the ranges of 10 6 A/cm 2 ).…”
Section: Resultscontrasting
confidence: 91%
“…Similarly, rapid enhancement in flux pinning and critical current density was observed in YBCO films by the incorporation of nanoparticles such as BaSnO 3 [9], BaHfO 3 [22] Ba 2 YTaO 6 [23], Ba 2 YNbO 6 [24,25] and Ba 2 RETaO 6 [26]. In our earlier works, we had reported the effect of addition of simple oxide, HfO 2 [27], ABO 3 type perovskite, nano BaHfO 3 [28,29] and double perovskite YBa 2 HfO 5.5 [30] tremendous improvement in flux pinning force and critical current density.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Unfortunately, bulk Y-123 suffers from low grain boundary conductivity, i.e., weak links and poor flux pinning, resulting in low J c in the presence of magnetic field [3], and its T c is sensitive to oxygen content in the system [4]. Therefore, many efforts have been devoted to overcoming these issues in order to achieve the J c and T c required for technological applications [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that perovskites could be beneficial for incorporation into YBCO due to their similar crystal structures relative to the host YBCO phase [9]. Thereafter perovskite based additions have gained renewed interest as a class of materials that can be incorporated into REBCO superconductor for dramatic improvements in the pinning properties [10][11][12][13]. And a number of perovskites like Sr 2 HoHfO 5.5 [14], GdBa 2 NbO 6 [15], Ba 2 ErZrO 5.5 [16], YBa 2 ZrO 5.5 [17], and so forth were being considered as substrate materials for YBCO film deposition.…”
Section: Introductionmentioning
confidence: 99%